2022
DOI: 10.3390/pharmaceutics14020293
|View full text |Cite
|
Sign up to set email alerts
|

Monoketonic Curcuminoid-Lidocaine Co-Deliver Using Thermosensitive Organogels: From Drug Synthesis to Epidermis Structural Studies

Abstract: Organogels (ORGs) are remarkable matrices due to their versatile chemical composition and straightforward preparation. This study proposes the development of ORGs as dual drug-carrier systems, considering the application of synthetic monoketonic curcuminoid (m-CUR) and lidocaine (LDC) to treat topical inflammatory lesions. The monoketone curcuminoid (m-CUR) was synthesized by using an innovative method via a NbCl5–acid catalysis. ORGs were prepared by associating an aqueous phase composed of Pluronic F127 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 67 publications
(95 reference statements)
0
6
0
Order By: Relevance
“…3 B) showed that the emulsion and PCL alone exhibited more of a liquid character than the gel formulations, considered to be pseudoplastic behavior. This pseudoplastic character shows that the gel reduces materials outflow, a favorable indicator for topical applications [ 39 , 40 , 52 , 53 ] as repellents must remain on the skin surface at the application site.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 B) showed that the emulsion and PCL alone exhibited more of a liquid character than the gel formulations, considered to be pseudoplastic behavior. This pseudoplastic character shows that the gel reduces materials outflow, a favorable indicator for topical applications [ 39 , 40 , 52 , 53 ] as repellents must remain on the skin surface at the application site.…”
Section: Resultsmentioning
confidence: 99%
“…The elastic Gʹ and viscous moduli G" were measured between 0 and 60 °C. Gʹ and G" measurements were also made with ω frequency from 0.1 to 10 Hz at 32.5 °C [ 39 ]. The flow curves σ (γ ˙) (“backward” and “forward”) were obtained at 32.5 °C with a shear rate γ ˙ ranging from 0 to 100 s −1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the studies on dynamics of polydisperse emulsions transport through microchannels and the development of complex models of The first case, known as "slug flow", is widely reported in the literature [14][15][16]. The analysis of the individual droplets transport, their deformation, and tearing in channels with a similar diameter, has gained particular interest within the formation of monodisperse emulsions, in various types of droplet generators [17,18]. The knowledge of the flow dynamics and the interactions between the phases and the channel wall proved to be extremely important for obtaining droplets of specific sizes [19].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoscale drug delivery systems (DDS) have been designed as inert systems that can transport drugs at the target site with high selectivity and controllable kinetic release profile [ 6 , 7 ]. Various DDS, such as niosomes, liposomes, transferosomes, and solid lipid nanoparticles, have already been employed to improve LID efficacy due to the role of these systems as skin permeation enhancers able to increase drug permeability, and consequently, ensure a higher drug accumulation at the target site and thus, an improved analgesic effect [ 8 , 9 , 10 , 11 ]. Their better permeation ability allows for lower drug doses and could reduce cardiovascular side effects [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%